Religious Aspects of Depression in the Elderly - Rahmadayani, Annisa; Boy, Elman; Achsanudin, Muhammad Rijal (MAGNA MEDICA Berkala Ilmiah Kedokteran dan Kesehatan, 2022)
Background: Elderly population (Elderly) is people who are aged 60 years and over. The increase in life expectancy leads to an increase in the number of elderly populations. This increase leads to an increased risk of physical and mental illness. The prevalence of the population suffering from depression in the elderly is 5 percent to 10 percent. Religious behavior seems to minimize stress levels, misbehavior, provide social support and help individuals find meaning in life.Objective: To find out the religious aspect of depression in the elderlyMethod: Type of study is a literature review. The literature search, both international and national, adapted to PICOT and journal search terms through MESH (Medical Subject Heading), restrictions on taking journals, and other things. Journal used in a literature review. This was obtained through the Scientific Indonesia journal provider database through Google Scholar. In this study, researchers used keywords according to MESH, namely "religiosity," "depression," "elderly," and selected full text.Result: Elderly is more than 60 years old. This is in accordance with the Minister of Social Affairs Regulation of Indonesia Number 05 of 2018 concerning Elderly Welfare. The high life expectancy in the elderly certainly increases the risk of mental and physical illness in the elderly. The quality of life in the elderly begins to decrease, which makes the elderly susceptible to depression.Conclusion: Depression in the elderly can be decreased by increasing the aspect of religiosity in the elderly.